Total gastrectomy with isoperistaltic jejunal interposition flap for symptomatic management of gastric polyposis from familial adenomatous polyposis - Srinivasa, Dhivya; Wray, Curtis J. (Journal of Gastrointestinal Oncology; Vol 5, No 1 (February 27, 2014): Journal of Gastrointestinal Oncology, 2014)
Patients with familial adenomatous polyposis (FAP) oftentimes have extracolonic polyps. The patient discussed in this case report had innumerable gastric polyps which were significantly affecting his ability to tolerate oral intake and his overall nutrition. Medical management was not sufficiently controlling his symptoms; therefore we proceeded with surgical intervention. We discuss the use of a total gastrectomy with an Isoperistaltic jejunal interposition flap for the symptomatic management of gastric polyposis. We describe the technique used and benefits to this specific procedure when it comes to long term outcome, complications, and monitoring.